Zooming in on the Chemistry of Protoplanetary Disks with ALMA. Issue Volume 13:Issue S332(2017) (4th September 2018) - Cleeves, L. Ilsedore
Abstract: During the first few ~Myr of a young stars life, it is encircled by a disk made up of molecular gas, dust, and ice – the building blocks for future planetary systems. How/when these disks form planets and what sets the planets initial compositions remain key outstanding questions in disk science. In recent years, major leaps in sensitivity and spatial resolution afforded by the Atacama Large Millimeter/Submillimeter Array (ALMA) have revolutionized our understanding of protoplanetary disks chemical composition and physical properties, revealing in some cases complex radial, vertical, and azimuthal structure in the dust and gas. In this contribution, I review recent observational results and new theoretical puzzles, and how these fit into a newly emerging picture of the disk environment.